Increasing fish biodiversity in high elevation Albertan lakes in response to global environmental change over the past 50 years - Wu, Thomas; Nguyen, Thi Nhi; Imrit, Mohammad Arshad; Kong, Jude; Sharma, Sapna (Frontiers in Ecology and Evolution, 2024)
The diversity of freshwater fishes is threatened by multiple environmental stressors, including climate change, alterations in land use, and introduction of non-native species. However, the quantification of temporal biodiversity in freshwater communities is limited. Here, we asked: i) how has alpha (species richness), beta (changes in freshwater species composition), and gamma diversity (total species diversity in a landscape) changed over time for lakes over a 50 year period?; and ii) What are the climatic, land use, and lake morphological drivers associated with higher diversity? We assembled a database of fish species occurrence from 20 lakes across subalpine and alpine regions in Alberta from 1970-2019, in addition to lake morphological, climatic, and land use characteristics of the watersheds. We observed an overall increase in alpha, beta, and gamma diversity from the 1970s to 2009s. However, all measures of diversity declined from 2010-2019. We found that more lakes and species assemblages were influenced by species gains, rather than species losses (with the exception of the last decade of sampling). Generally, we found that coolwater species were expanding and coldwater fishes were being lost throughout our study lakes. We highlight temporal heterogeneity in fish biodiversity responses to substantial environmental pressures in this region.